Implementasi Smart Lighting IoT Lapangan Voli dengan NodeMCU dan Blynk untuk Kontrol RGB - Anis Nurcahya; Enang Rusnandi; Raden Deden Ahmad Hidayat (Journal of Multimedia Technology and Applied Software, 2026)
Lighting on a volleyball court plays a critical role in ensuring visual comfort and player safety during evening training sessions and matches. However, many existing installations still rely on conventional, manually operated lighting that lacks dynamic control over color and intensity, limiting both user experience and energy efficiency. This study proposes the design and implementation of an Internet of Things (IoT)–based smart lighting system for a volleyball court that incorporates color-control capabilities using RGB LED luminaires. The system is built on a NodeMCU (ESP8266) microcontroller as the main controller, a Wi‑Fi network for communication, and the Blynk application as a mobile interface for remote operation. The research follows a system design and development methodology, covering requirements analysis, hardware–software co‑design, implementation, and experimental evaluation. Test results demonstrate that the system can reliably control on/off status, brightness levels, and RGB color in real time through the Blynk interface while maintaining stable wireless connectivity. These findings indicate that the proposed IoT-based smart lighting solution simplifies lighting management, enhances the flexibility of illumination, and offers potential gains in energy efficiency, making it a promising approach for modern, efficient, and interactive volleyball court lighting. Keywords: Internet of Things; smart lighting; NodeMCU; RGB LED; Blynk